P05 Inpatient management of alcohol related liver disease: too costly to ignore. (20th September 2022) - Turner, Lucy; Hussain, Mehvish; Rowe, Ian; Parker, Richard
Abstract : Introduction: Alcohol related liver disease (ARLD) is common worldwide and a frequent cause of ill health and death. Admissions to hospital related to this are commonplace: almost 980'000 admissions to hospital in 2019/2020 were linked to alcohol; this represents 5.7% of all hospital admissions in England1. Aim: To establish the cost of inpatient admissions related to alcoholic hepatitis and decompensated alcohol related liver cirrhosis. Methods: The electronic health records of patients with ARLD were examined retrospectively to identify: hospital admissions within the past three years, the primary cause of the admission and the length of stay. Those admitted with alcoholic hepatitis or decompensated liver disease were identified and cost analysis was undertaken. Decompensated liver disease was defined as: ascites, variceal bleeding, hepatic encephalopathy, alcoholic hepatitis or hepato-renal syndrome. Data were analysed with independent T-test. Results: One-hundred and fifty eight patient records were analysed. 12 patients were admitted with alcoholic hepatitis a total of 15 times. 10 patients were admitted with decompensated cirrhosis a total of 16 times. The mean cost of admission was £16'338.33 for alcoholic hepatitis, compared with £12'285.19 for decompensated cirrhosis (p=0.135). Mean length of stay was longer in those with alcoholic hepatitis, 30.3 days (range 6–68), compared with decompensated cirrhosis, 10.8 days (range 3–34) p=0.0008. Conclusion: Inpatient management of ARLD is commonplace and costly. We have previously demonstrated that intervention following detection of ARLD can alter the natural history. These data highlight the further importance of detecting liver disease in persons with alcohol use disorder and funding treatments in order to prevent the long-term sequelae.